Hydrophobic Interactions of the Structural Protein GRP1.8 in the Cell Wall of Protoxylem Elements - Ringli, Christoph (American Society of Plant Physiologists, 2001)
The glycine-rich structural protein GRP1.8 of French bean (Phaseolus vulgaris) is specifically localized in the modified primary cell walls of protoxylem elements. Continuous deposition of GRP1.8 into the cell walls during elongation growth of the plant suggests that GRP1.8 is part of a repair mechanism to strengthen the protoxylem. In this work, a reporter-protein system was developed to study the interaction of GRP1.8 with the extracellular matrix. Fusion proteins of a highly soluble chitinase with different domains of GRP1.8 were expressed in the vascular tissue of tobacco (Nicotiana tabacum), and the chemical nature of the interaction of these fusion proteins in the cell wall compartment was analyzed. In contrast with chitinase that required only low-salt conditions for complete extraction, the different chitinase/GRP1.8 fusion proteins were completely extracted only by a nonionic or ionic detergent, indicating hydrophobic interactions of GRP1.8. The same interactions were found with the endogenous GRP1.8 in bean hypocotyls. In addition, in vitro experiments indicate that oxidative cross-linking of tyrosines might account for the insolubilization of GRP1.8 observed in later stages of protoxylem development. Our data suggest that GRP1.8 forms a hydrophobic protein-layer in the cell wall of protoxylem vessels.